Baggage reclaim: Some thoughts on feminism and painting. (1st April 2017) - Fortnum, Rebecca
This article calls for a reappraisal of the feminist discussion around painting in relation to contemporary practices by women, suggesting that all painting by women has something to offer feminist critical thought. Playfully using Judy Chicago's reflections and strategies as a frame, the article explores how contemporary painters have engaged with the histories and communities of women to form new models of scholarship and practice. It examines the projects of painters Melissa Gordon, Nadia Hebson and the Obscure Secure group (Jacqueline Utley, Hayley Field and Claudia Böse) whose artwork forms a 'live' response to the legacy of little known and undervalued women artists. The article concludes by examining the notion of the painterly gesture and develops a feminist context in which to examine the materiality and processes of painting, with reference to the perspectives of Dana Schutz and Jutta Koether among others. It suggests Helen Molesworth's historically defined quality of ambivalence can be seen resurfacing as a critical position within contemporary painting by women.